Fooling some of the people all of the time : a long short story - Einhorn, David (Hoboken, N.J. : J. Wiley, 2008)
In 2002, Einhorn spoke publicly about Allied Capital--a leader in the private finance industry--presenting it as an excellent short opportunity. Einhorn describes the incredible events that followed his speech and how Allied and the investment community attacked him to protect the company--and its stock price. Informative and intriguing, "Fooling Some of the People All of the Time" details how the current environment on Wall Street--and the world of hedge funds in particular-- not only allows for such behavior, but how it protects the companies and attacks those who attempt to uncover them.--From publisher's description.
Includes index.
Einhorn, David was the founder of Greenlight capital. there's also a foreword by Joel Greenblatt.
nif 25/04/13
Loans
Keywords: Small business investment companies; Small businesses